2019
DOI: 10.18488/journal.26.2019.82.62.67
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Particulate Matter (PM) Evaluation in Gasabo District, Rwanda

Abstract: Contribution/Originality: This study is one of very few studies which have investigated the level of ambient particulate matter (PM) in Kigali. As result, it will help to reduce air pollutants concentration in Kigali for better human health and environmental protection in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…& Ishigaki, 2020). The majority of air pollution emissions in Rwanda are a result of the transport sector, including vehicle emissions, manufacturing industrial activities, such as cement and steel mills, quarrying activities that introduce dust in air, domestic cooking, soilblown dust, and waste combustion (Irankunda, 2019;Nduwayezu, Ruffo, Minani, Munyaneza, & Nshutiyayesu, 2009). The aim of this research was to assess imprints of domestic use of solid fuels (firewood and charcoals) burning on Particulate Matter PM2.5 and PM10.…”
mentioning
confidence: 99%
“…& Ishigaki, 2020). The majority of air pollution emissions in Rwanda are a result of the transport sector, including vehicle emissions, manufacturing industrial activities, such as cement and steel mills, quarrying activities that introduce dust in air, domestic cooking, soilblown dust, and waste combustion (Irankunda, 2019;Nduwayezu, Ruffo, Minani, Munyaneza, & Nshutiyayesu, 2009). The aim of this research was to assess imprints of domestic use of solid fuels (firewood and charcoals) burning on Particulate Matter PM2.5 and PM10.…”
mentioning
confidence: 99%
“…Results showed that air pollutants were present around the considered area that is why the appropriate mitigation and management strategies concerning these pollutants were highly recommended as the contribution of this paper. emissions in country came from transport sector including vehicle emissions; manufacturing industrial activities such as cement, and steel mills; quarrying activities which introduce dust in air; domestic cooking; soil-blown dust: and waste combustion (Elisephane, 2019;Nduwayezu, Ishimwe, Niyibizi, & Ngirabakunzi, 2015;Rema, 2018). In this Paper the main objective was focused on the effect assessment of the industrial activities on air pollution at CIMERWA cement factory one of the biggest industries in Rwanda and its surrounding areas.…”
mentioning
confidence: 99%